Brangäne: a new family of Barbarian asteroids. Issue 1 (14th February 2019) - Cellino, A; Bagnulo, S; Tanga, P; Devogèle, M; Bendjoya, Ph; Reilly, E; Rivet, J-P; Spoto, F
ABSTRACT: The so-called Barbarian asteroids [from the name of the prototype of this class, asteroid (234) Barbara] are extremely interesting objects because they might be the survivors of a very early generation of planetesimals. We have identified in the past the first case of an asteroid family (the Watsonia family) whose members are Barbarians, all issued from the collisional disruption of a sizeable parent body. Here we report on the identification of another family, called after the name of its biggest member, asteroid (606) Brangäne, consisting of objects displaying the polarimetric properties characterizing the Barbarian behaviour. This is the first recognized case of a swarm of small Barbarians issued from a quite recent cratering event.